2014
DOI: 10.1111/jgs.12890
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Utility Analysis of a Pharmacotherapy Follow‐Up for Elderly Nursing Home Residents in Spain

Abstract: Pharmacotherapy follow-up is considered cost-effective for elderly NH residents in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…In this study, we saw a drop in the number of drugs for both groups, although this tendency was greater among the older adults in the IG (0.28 drugs; p<0.001) than for those in the CG (0.07 drugs; p=0.063). In a recent study of a MRF service for nursing home residents in Spain [36], pharmacist interventions reduced the mean number of prescribed medications by 0.47 drugs (p<0.001), whereas the mean number of prescribed medications increased by 0.94 drugs in the CG (p<0.001). Participants were residents aged 65 or over, but their health state was worse than in the case of the participants in the present study, and this may explain why that intervention was more effective in optimizing prescribed medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we saw a drop in the number of drugs for both groups, although this tendency was greater among the older adults in the IG (0.28 drugs; p<0.001) than for those in the CG (0.07 drugs; p=0.063). In a recent study of a MRF service for nursing home residents in Spain [36], pharmacist interventions reduced the mean number of prescribed medications by 0.47 drugs (p<0.001), whereas the mean number of prescribed medications increased by 0.94 drugs in the CG (p<0.001). Participants were residents aged 65 or over, but their health state was worse than in the case of the participants in the present study, and this may explain why that intervention was more effective in optimizing prescribed medication.…”
Section: Discussionmentioning
confidence: 99%
“…Jódar-Sánchez et al [36] evaluated the cost-effectiveness of a MRF service for older adult residents in nursing homes in Spain, obtaining an adjusted ICER of €6,574/QALY (in the more realistic scenario).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies were located in the United States, UK and Australia with smaller numbers from the Netherlands, Canada and Belgium . Twelve papers reported randomised controlled trials, and five were non‐randomised controlled studies, with the remainder pre‐/post‐uncontrolled interventions conducted as service evaluations. Papers ranged in publication dates from 1978 to 2019, and all services reported positive outcomes with respect to their main aim.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen papers stated that the pharmacist delivering the service was a ‘consultant’, and twelve papers noted that the pharmacist was described as ‘clinical’ . Five papers reported that the pharmacist had completed an accreditation process, one of which described the training as consisting of consultation skills, identification of drug‐related problems, guidelines and how to create pharmaceutical care plans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation